Trauma care and specialized treatment of injured patients with gunshot fractures of the humerus in the medical support system for Joint Forces Operation - I. P. Khomenko; I. A. Lurin; S. O. Korol; A. M. Halushka; K. O. Hrebennikov (Zaporožskij Medicinskij Žurnal)
Gunshot fractures of the humerus account for 20.3–22.3 % of all bone fractures. The problem of choosing the treatment tactics for the patients with gunshot fractures of the humerus is due to an the increase in their severity and increase in the frequency of complications requiring a lengthy reconstructive surgery.